INCREASING THE CONFIDENCE OF PSBA UNZAH GENGGONG STUDENTS THROUGH DIRECT PRACTICE-BASED ARABIC MUHADASAH WITH A COMMUNICATIVE APPROACH - Khusni, Achmad Robith; Sulaiman, Mahfudz (SHAWTUL ARAB, 2025)
This study aims to analyze the muhadasah Arabic direct practice with communicative approach or communicative language teaching in students of the Center for Foreign Language Studies of Islamic University Zainul Hasan Genggong. Of the four Arabic skills that are no less important are speaking skills. This skill is a major component in learning a foreign language. The application in learning Arabic is very much but the most interesting is learning with a communicative approach because students are not only trained to memorize but are trained to speak actively. Qualitative approach and case studies are research methods in this article the subjects of this study are Arabic teachers, Director of the Center for Foreign Language Studies, and students accompanied by observations in everyday learning on campus. The result is that communication-based language teaching methods are able to increase students ' self-confidence and active involvement. Although there are still some vocabulary that has not been mastered, students still dare to get used to communicating everyday. This combination of games and methods creates a more lively and interesting learning atmosphere. Therefore, this method is very suitable for use in teaching Arabic.